MENGEMBANGKAN BISNIS MASKER KAIN SEBAGAI PELUANG USAHA DI MASA PANDEMI COVID - Lydiawati Soelaiman (PROSIDING SERINA, 2021)
Laila Collection, which is engaged in clothing sewing services, is one of many MSMEs who got impact from the Covid-19 pandemic. The orders have decreased dramatically due to restrictions on activities in the community. This is increasing due to changes in consumer consumption since the pandemic that chooses health products over fashion. Based on these conditions, this activity aims to help Laila Collection to survive in current conditions by utilizing the opportunities and resources currently available. The activity begins with identifying business opportunities with the results of the cloth mask business as a promising business. Consumer demand for cloth masks is quite high because consumers not only use cloth masks as personal protection equipment but are also more costeffective because they can be washed and appear more fashionable. Further activities include determining the market segment to be addressed so that the design of the product is more targeted, the creation of fabric mask product designs that have unique values and how to do online marketing. The results obtained from this activity are that the owner of Laila Collection can take advantage of the current opportunity by producing cloth masks that have unique designs. In addition, this activity also raises awareness of MSME owners to use online marketing, both social media and marketplace